2011
DOI: 10.1002/jso.23013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and function of decreased FOXO1 in renal cell carcinoma

Abstract: Reduced expression of FOXO1 is common in RCC and a potentially suitable marker of different histological subtypes and prognosis of cRCC. Increasing expression of FOXO1 by the miR-27a inhibitor could prevent cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(45 reference statements)
2
20
0
Order By: Relevance
“…Although it has been reported that FoxO1 positively regulates LAL expression in adipocytes, FoxO1 is negatively regulated by Akt and down‐regulated in the majority of human renal tumour samples . Thus, we applied IHC to compare LAL, FoxO1 and phosphorylated Akt (p‐Akt) (Ser473) and total Akt protein levels in adjacent slices of kidney and ccRCC samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been reported that FoxO1 positively regulates LAL expression in adipocytes, FoxO1 is negatively regulated by Akt and down‐regulated in the majority of human renal tumour samples . Thus, we applied IHC to compare LAL, FoxO1 and phosphorylated Akt (p‐Akt) (Ser473) and total Akt protein levels in adjacent slices of kidney and ccRCC samples.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been reported that FoxO1 positively regulates LAL expression in adipocytes, 44 FoxO1 is negatively regulated by Akt and down-regulated in the majority of human renal tumour samples. 45,46 Thus, we applied IHC to compare LAL, FoxO1 and phosphorylated Akt (p-Akt) (Ser473) and total Akt protein levels in adjacent slices of kidney and ccRCC samples. Interestingly, the level of p-Akt exhibited a negative correlation with FoxO1 ( Figure 4A) and a strong positive correlation with LAL ( Figure 4A, B) (P < .05).…”
Section: Suppression Of Lal Attenuates Ccrcc Growth and Survival Bymentioning
confidence: 99%
“…A transcriptome analysis of YM155-treated RCC786.0 cells identified up to 200 genes that were differentially expressed in the presence of YM155, the majority of which were associated with the p53 connection pathway and would thus affect survivability, cellular proliferation and cell cycle control. Of these genes, we followed up on four members (tumour suppressors FOXO1 and CYLD ; tumour promoters ID1 and BIRC5 ) that were involved in RCC pathology [5,38,41,45,59,60,61]. BIRC5 encodes survivin expression [48,49,50] and FOXO1 mediates cell cycle arrest and promotes apoptosis [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The rs895819, as an oncomiR, exhibited its oncogenic activity through regulating target genes [60, 61]. It means that down-regulation of miR-27a may contribute to decreased cancer risk through up-regulating the targets.…”
Section: Discussionmentioning
confidence: 99%